Phylogenetic tree and characteristics of endophytic bacteria associated with Theobroma cacao L. in a zone of Esmeraldas Province, Ecuador (Bioagro, 2021)
Given the importance of using endophytic bacteria for the control of cocoa diseases, the objective of this study was to build the phylogenetic tree and characterize the endophytic endospore-forming bacteria based on the cropping altitude, age and tissue of the cocoa plant in a producing area of the Esmeraldas province, in Ecuador. The isolation of bacteria was done from healthy pods and flower pedicels from cocoa Criollo Type Nacional cultivar. Forty-five endospore forming endophytic bacteria were recovered from healthy pods and flowers pedunculus, mainly from endocarp. No association was found between the number of bacterial isolates and the age of the fruit, although there was a slight tendency for the isolates to decrease towards the higher altitude sites.
Keywords: Bacillus; biocontrol; cocoa; endocarp; flower pedicel